Paloma Gay y Blasco a Martin Fotta (eds.): Romani Chronicles of COVID-19: Testimonies of Harm and Resilience: New York, Oxford: Berghahn Books, 2023, 314 s., ISBN 978-1-80073-893-5 - Szénássy, Edit (Romano džaniben, 2023)
RECENZE